Human resource policies and older workers - Ang, Joo Kim (2013)
This study explores the needs of older workers and the extent to which the companies in Singapore have adapted their human resource policies and practices to meet these needs. More specifically, it attempts to find out the adequacy of the policies, age discriminatory practices, and the attitudes of employers towards older workers. Three companies from three industries in Singapore were used as case-studies. The study employs a qualitative-based case study approach and covers organisations in the marine, manufacturing and service industries. Moreover, it reviews the literature on human resource practices and strategies required for effective management of human resources, and in particular older workers.